Successful Pulmonary Endarterectomy after Acute Pulmonary Embolism and Reversal of Acute Cor Pulmonale in an 11-Year-Old Boy with Nephrotic Syndrome - Onyekachukwue Osakwe; Bibhuti B. Das (MDPI AG, 2022)
Patients with nephrotic syndrome (NS) are at an increased risk for thromboembolic events, such as deep venous and arterial thrombosis and pulmonary embolism (PE). In general, PE in children differs from adults in incidence, predisposition, pathophysiology, presenting symptoms, and management strategies. There is a lack of treatment guidelines for PE in children, and the management strategies are mostly extrapolated from adult data. This case report highlights the presentation of acute cor pulmonale due to massive PE associated with NS and a successful pulmonary endarterectomy that reversed the child's pulmonary hypertension and normalized right ventricular function.